TECHNOLOGY FOR DEVELOPMENT AND SUBSTANTIATION OF THE SEMANTIC COMPONENT OF THE PROFESSIONAL PROFILE OF ANOFFICER-PSYCHOLOGIST OF THE ARMED FORCES OF UKRAINE - Yurkov, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The professional profile of an officer-psychologist of the Armed Forces of Ukraine clearly defines the activities of specialist, the dominate type of activities in his work, and qualities that ensure the successful performing of duties. The professional profile of an officer-psychologist of the Armed Forces of Ukraine generally answers the following questions: what activity is analyzed and what is the subject and purpose of this activity, what are the criteria for assessing the effectiveness of professional activities; what are the factors that affect the psyche of military specialist; what are the special requirements for soldiers. According to the results of the questionnaire survey of experts the professionally important qualities of readiness of the officer-psychologist for professional activity in the Armed Forces were determined on the basis of the obtained and mathematically processed results of the questionnaire. The indicators of professionally important (necessary) qualities were determined, namely moral-volitional and emotional traits of an officer-psychologist of the Armed Forces of Ukraine. The competencies, that are acquired during the formation of the readiness of future psychologists for professional activity in the Armed Forces and should be formed as a result of professional training, have been developed on the basis of scientific and practical analysis. They are the following: the navigate in difficult combat situations, the ability to take optimal decisions and set tasks to subordinate units in a combat situation based on the analysis of received information, the assessment of the situation and ability to provide tactical calculations, the ability to develop and maintain combat documents and records. The professional profile of the officer-psychologist of the Armed Forces of Ukraine clearly defines the activities of specialist, the dominate type of activities in his work, and qualities that ensure the successful performing of duties. The training of a modern officer-psychologist of the Armed Forces of Ukraine is aimed at ensuring the harmonious development of the personality of an officer of the Armed Forces of Ukraine, that implies the development of all potential opportunities inherent in a specialist. The military psychologist should be prepared for the practical activities as a result of mastering of professional knowledge, skills and abilities (planned result of education), theoretical competence, the formation of professional competencies of a soldier.
Keywords: рrofessional profile of an officer-psychologist, Armed Forces of Ukraine, professional training of soldiers, theoretical training, knowledge, skills and abilities